In vitro Characterisation of an Injectable Composite Graft Material Synthesised from Collagen Extracted from Fish Scales and Eggshell-Derived Hydroxyapatite - Prathap, Sruthy; Shankar, Rajesh Kashyap; Thomas, Nebu George; Venkatesan, Jayachandran; Kizhakkethil, Binsi Puthanpurakkal; Surya, Suprith; Sreekantantan, Prathap Mulackal (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim/Background: Collagen and hydroxyapatite have been used as scaffold for bone repair encouraging cell adhesion and growth. Composites synthesized from hydroxyapatite and collagen mimic biomechanical properties of natural bone. Extensive efforts have been made to fabricate graft materials from natural sources to mimic biochemical and biomechanical properties of natural bone. The present study is aimed to synthesise a composite graft from eggshell derived hydroxyapatite and fish collagen and characterize the novel material. Materials and Methods: The composite graft material was prepared using eggshell derived hydroxyapatite (60%) and fish derived collagen (40%) by lyophilisation. The prepared novel material was characterised using FTIR, XRD and SEM Cell viability was assessed using MTT assay. The material is then mixed with a suitable binder (glycerol). Results: The FTIR and XRD analysis confirms a composite material of hydroxyapatite- collagen composite graft. The ratio of hydroxyapatite to collagen was 60: 40. Crystallinity of the hydroxyapatite was not disrupted by the collagen. The collagen particles agglomerated with each other as well as on hydroxyapatite particles according to SEM. The composite graft was found to be noncytotoxic. Conclusion: In the present study eggshell derived hydroxyapatite and fish collagen has been used to synthesize a composite graft. Glycerine has been used as a binder to improve the properties. The prepared novel composite material exhibited good cell viability and may be effectively used as an alternative to conventional bone substitutes.
Keywords: Bone graft; Composite; Eggshell; Hydroxyapatite; Fish Collagen; Characterisation